Association of SOD1 and SOD2 single nucleotide polymorphisms with susceptibility to gastric cancer in a Korean population. Issue 3 (8th August 2012) - Han, Lin; Lee, Suk Woo; Yoon, Jung Hwan; Park, Yong Gyu; Choi, Yoo Jin; Nam, Suk Woo; Lee, Jung Young; Wang, Yin Ping; Park, Won Sang
<x xml:space="preserve">Abstract</x> Oxidative stress is accepted as one of the main factors involved in the development and progression of cancer. Superoxide dismutases (SODs) are important in avoiding oxidative stress by eliminating reactive oxygen species (ROS). To determine whether single nucleotide polymorphisms at G7958A within SOD1 and at T5482C within SOD2 are associated with an increased susceptibility to gastric cancer, we investigated the genotype and allele frequencies of the genes from 294 gastric cancer patients and 300 healthy individuals. A polymerase chain reaction‐single strand conformation polymorphism assay was used to identify the SOD1 G7958A and the SOD2 T5482C genotypes. Statistically significant differences in the genotype and allele frequencies of SOD2 T5482C were found between the healthy controls and gastric cancer patients (p = 0.0001 and p < 0.0001, respectively). When the data were stratified according to gastric cancer histological subtypes, the risk of both diffuse‐ and intestinal‐type gastric cancer was statistically higher for carriers of the C allele compared with carriers of the T allele. However, there were no statistically significant differences in genotype distribution (p = 0.5069) and allele frequencies (p = 0.3714) of SOD1 G7958A between gastric cancer patients and controls. Our findings suggest that polymorphism of the SOD2 T5482C may be closely associated with an increased susceptibility to the development and differentiation of gastric cancer in the Korean population.